Pengaruh Budaya Organisasi, Gaji dan Kesejahteraan Karyawan terhadap Kinerja Karyawan BPBD Kab. Nganjuk - Rara Zumna Septianingrum; Indah Listyani; Rike Kusuma Wardhani (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
Employee performance is the result of the work carried out by the employee to fulfill their duties and responsibilities in accordance with the discipline entrusted to them. This research aims to determine and analyze organizational culture, salary, and employee welfare on the performance of employees at the BPBD of Nganjuk Regency. The method used is a quantitative approach with causal research, which is capable of explaining the cause-and-effect relationship between variables. Research data was obtained through the distribution of questionnaires to 50 respondents who are employees of the BPBD of Nganjuk Regency. To ensure data quality, a series of tests were conducted including validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R2) which were processed using SPSS version 25. The research results show that organizational culture has a significant influence on employee performance, indicating that the stronger the applied organizational culture, the better the resulting employee performance will be. Salary also proves to significantly affect employee performance, which shows that providing a decent salary in accordance with job responsibilities can enhance the resulting employee performance. Likewise, employee welfare significantly influences employee performance, indicating that employee welfare, both physically and psychologically, can improve the resulting employee performance. Simultaneously, these three variables have an effect on employee performance. The coefficient of determination value of 0.693 indicates that 69.3% of the influence on the employee performance variable comes from company culture, salary, and employee welfare, while 30.7% comes from other external factors